Menyalurkan Informasi dan Meninjau Gangguan Produktivitas TBS Kebun Sawit Penduduk di Desa Saliki (Kecamatan Muara Badak, Kabupaten Kutai Kartanegara): Channeling Information and Reviewing FFB Productivity Disruptions Residents' Palm Oil Gardens in Saliki Village (Muara Badak District, Kutai Kartanegara Regency) - Surya Darma (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The productivity of fresh fruit bunches (FFB) of independent plasma plantations owned by residents of Saliki Village, located in Muara Badak District (Kutai Kartanegara), is only around 1 ton/ha/month. This gain is much smaller than the productivity level of the oil palm plantations managed by the company. In the last two years, the increase in FFB prices has spurred farmers to increase the productivity of their oil palm plantations by investigating the decline in the productivity of their plantations with other more competent parties. The soil analysis findings showed that the macronutrient content of N and K2O was low, and it classified P2O5 as low, a limiting factor for productivity. Early fertilization until 6-8 years is dominant, with compound fertilizer (15N:15P:15K) as the key attribute that implies a non-compliance with the recommended dose. When the age of planting increases, but there is an imbalance of nutrients, it will affect low productivity. The lack of understanding and knowledge of farmers causes this assumption about nutrient content and the use of fertilizers. The implementation method is supported through a comprehensive technical guidance with oil palm FFB farmers in the selected area within 2 sessions. After the field meeting, the researcher recommended the relevant dose of fertilization (kg/tree/year). Through this discussion, the researchers disseminated valuable insights to oil palm farmers in order to stimulate, strengthen references, and identify types of fertilizers that are in line with the nutrients and content in the palm oil fertilization phase in order to improve FFB productivity.